A Multisite, Multidisciplinary Delphi Consensus Study Describing "Usual Care" Intervention Strategies for School-Age to Transition-Age Youth With Autism. (29th March 2019) - Kerns, Connor M.; Moskowitz, Lauren J.; Rosen, Tamara; Drahota, Amy; Wainer, Allison; Josephson, Anne R.; Soorya, Latha; Cohn, Elizabeth; Chacko, Anil; Lerner, Matthew D.
Abstract : Understanding usual care is important to reduce health disparities and improve the dissemination of evidence-based practices for youth (ages 7–22 years) with autism spectrum disorder (ASD). A barrier to describing "usual ASD care" is the lack of a common vocabulary and inventory of the practices used by a diverse provider field. To address this barrier, we gathered input from expert providers to develop an inventory of usual care practices and assess expert familiarity and perceptions of these practices as interventions for anxiety, externalizing, and social difficulties in ASD. Purposeful sampling recruited 66 expert ASD providers representing multiple disciplines from 5 sites. Via a 2-round Delphi poll, experts reviewed, suggested revisions to and rated 49 literature-derived practices on several dimensions (familiarity, usefulness, common use, research support). A revised list of 55 practices and anonymous summary of group characteristics and ratings was then returned for further review. Results yielded 55 intervention practices, 48 of which were identified as "familiar" approaches by consensus (≥ 75% endorsement). Greater variation was observed in practices identified by consensus as most often used, useful, and research supported, depending upon the target problem. Findings provide an inventory of practices, reflective of the multidisciplinary language and approaches of expert ASD providers. This inventory may be used to better assess what constitutes usual care for youth with ASD in the United States. Moreover, findings offer insights from clinical experts regarding the range and acceptability of practices that may inform and ground treatment research, dissemination, and implementation efforts.